The subject of waves in a new approach introductory steps of a Design Based Research (DBR) - Finta, Zs; Jenei, P; Schramek, A (Journal of physics. Conference series, 2021)
Based on years of teaching, our team aims to elaborate a modern experimental manual with a modular structure meant to entwine the features of a traditional book on paper support with the advantages of an e-book. The chapter on the Wave Theory has been written as a start-up. In our vision, the core material of the manual is targeting those high-school students who do not wish to study Physics on a higher level, meanwhile the extensions to the lessons (such as the simulations, high-level extra information and any other attractive topics etc.) are for the students who are interested in Physics and who are thus given the possibility of a more profound study. The traditional manual would be designed to cover the core material, and the extensions would be made accessible via smartphones, as well as the QR-codes placed in the lessons. The webpage that has been added to the online version includes the written lessons, the extensions being placed into so-called boxes. Approach to the chapter largely differs from any previous approaches as the wave types are presented along with the description of the related wave phenomena. Practicality and efficiency testing of the webpage is ongoing in a rather close circle via questionnaires and a multiple choice test, the manual to be continuously improved and amended subsequent to the feedback we receive and according to our own teaching experiences..